ANALISIS PENGARUH KESADARAN MEREK, ASOSIASI MEREK, PERSEPSI KUALITAS DAN LOYALITAS MEREK TERHADAP PREFERENSI MEREK DAN NIAT BELI PADA PASTA GIGI CLOSE UP DI SURABAYA - PRAYOGO HASYIM, ALEX (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The purpose of this study was to determine how the variables influence brand awareness, brand associations, perceived quality, and brand loyalty influence on brand preference and purchase intention in Close Up toothpaste in Surabaya. Analysis techniques used in this study is the Structural Equation Modeling. Sampling technique used was non-probability sampling which are not randomly drawn and focused on customer Close Up, the sampling technique used was purposive sampling with the criteria of at least 17 years of age, as well as in the first years routinely use Close Up toothpaste. The research proves that the brand awareness and brand loyalty has no effect on brand preference, while the perceived quality and brand associations influence brand preference, and than brand preference influence a consumer's purchase intention Close Up toothpaste in Surabaya. Conclusions can be drawn from this study is that the positive influence of brand associations on brand preference, the positive influence of perceived quality of brand preference, brand preference and positive influence on purchase intention is received, while the positive effect of brand awareness to brand preference and brand loyalty is a positive influence on preference brands are not acceptable.